Effect of Hydroxyapatite Filler on Mechanical Properties of PE/HAp Composite as a Candidate for Bone Repair - Qulub, Fitriyatul; Wardhani, Inten Firdhausi (Indonesian Applied Physics Letters, 2024)
Polymer is one material that can be used as a fixation to repair fractured or broken bones. However, polymers are soft and ductile, so modifying them by adding hydroxyapatite as a filler is necessary. Polyethylene is a high density polymer with more potent material properties to be utilized as a matrix. The PE-HAp composites were synthesized by compacting and heating the composition percentage of Hap 25%, 35% and 45%. Based on the characterization results using XRD, FTIR, and hardness test instruments, it is concluded that the addition of HAp composition results in better composite mechanical properties. The material properties are improving, increasing the hardness value (shore A) by 63 shore A. The hardness value increases because the composite properties are more compact, and the PE matrix physically binds the HAp filler. This is reinforced by XRD and FTIR characterization results, with no new compounds formed and no new molecular vibrational patterns in the FTIR spectrum.